The The Perspective of Wealth on Crypto Assets Based on the Qur’an and Hadith - Asnan Purba; Ahmad Hasan Ridwan; Moh. Najib (Faculty of Islamic Business and Management, 2026)
This study addresses the growing juridical and ethical challenges surrounding crypto assets within Islamic law, particularly the absence of an integrated and auditable framework for determining their status as wealth (al-māl). Existing studies predominantly focus on general halal–haram judgments, single-token analyses (such as Bitcoin or stablecoins), or regulatory and fatwa-based discussions, without systematically mapping different crypto token typologies against classical fiqh definitions of wealth and Qur’anic–Sunnah-based positions of property. This gap results in fragmented legal reasoning and normative uncertainty in Sharīʿah decision-making. The objective of this research is twofold: first, to construct a Sharīʿah evaluation matrix that assesses five types of crypto tokens (utility tokens, security tokens, asset-backed tokens including stablecoins, DeFi tokens, and NFTs) based on the definitions of wealth according to the four Sunni schools (Ḥanafī, Mālikī, Shāfiʿī, and Ḥanbalī) using five classical indicators—ta‘yīn (clarity of object/right), qīmah (lawful value), qabd (delivery/possession), manfa‘at mubah (lawful benefit), and dhamān (liability). Second, the study maps each token’s compliance with the five Qur’anic positions of wealth ownership of Allah, trial, trust, means of worship, and productive wealth within the normative boundaries of the 2021 Indonesian Council of Ulama (MUI) ruling. Employing a juridical–normative research design with qualitative content analysis, this study examines Qur’anic verses, Prophetic traditions, classical fiqh doctrines, contemporary scholarly literature, fatwas, and technical documentation of crypto tokens. The discussion integrates classical jurisprudential principles with operational and market-based evidence to ensure doctrinal validity and practical applicability. The findings indicate that crypto assets cannot be judged uniformly; their Sharīʿah status depends on the clarity of rights, underlying value, delivery mechanisms, benefit legality, and enforceable liability. Asset-backed tokens and certain security tokens demonstrate the highest potential for conditional permissibility, while utility tokens, DeFi tokens, and NFTs require stricter Sharīʿah controls due to higher risks of speculation, uncertainty, and governance deficiencies. The integration of classical indicators with maqāṣid-based wealth positions provides a consistent, transparent, and auditable framework for determining whether crypto assets are permissible, conditionally permissible, or prohibited under Islamic law.